2021
DOI: 10.3390/healthcare9030316
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Working in Nursing Homes: A Mediation Model for Work Engagement Based on Job Demands-Resources Theory

Abstract: This study examined the impact that the attractiveness of working in nursing homes and autonomous clinical judgment have on affective occupational commitment, and whether work engagement mediates these relationships. This analysis was based on the job demands-resources theory. The study setting was 1200 nursing homes (including long-term care welfare facilities and long-term care health facilities) in eastern Japan. An anonymous, self-report questionnaire survey was administered to two nurses from each facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Intrinsic motivation was one of the factors that had a significant effect on work engagement, which supported the results of previous studies [34,68]. In this study, four intrinsic motivation items were investigated as follows: (1) Interested in community medicine, (2) Wanting to practice basic nursing, (3) Interested in gerontological nursing, and (4) Careful nursing care.…”
Section: Impact Of Work Motivation On Work Engagementsupporting
confidence: 84%
“…Intrinsic motivation was one of the factors that had a significant effect on work engagement, which supported the results of previous studies [34,68]. In this study, four intrinsic motivation items were investigated as follows: (1) Interested in community medicine, (2) Wanting to practice basic nursing, (3) Interested in gerontological nursing, and (4) Careful nursing care.…”
Section: Impact Of Work Motivation On Work Engagementsupporting
confidence: 84%
“…Alternately, Job resources refer to every aspect of job that is reducing job demands and aiding work engagement. Hara et al (2021) identified salary as the stimulating factors of work engagement among nurses working in nursing homes. Unlike in other countries, China's nurses working in nursing homes are older, maybe a good health status will lead to a better work performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to job satisfaction, the following personal resources were identified as significant direct or indirect predictors of the nursing staff's WE-'sense of coherence' (SOC) (Malagon-Aguilera et al, 2019), 'mindfulness' (Janssen et al, 2020), 'intrinsic work motivation' (Zeng et al, 2022), 'the sense of performing good care', 'willingness to learn good care', 'confidence in my ability' and 'well-being' (Kameyama et al, 2022), 'autonomous clinical judgement' (Hara et al, 2021), and 'trait emotional intelligence' (EI) (Toyama & Mauno, 2017). It should be noted that the significant bivariate correlation between SOC and WE in the study of Malagon-Aguilera et al (2019) was not confirmed by the linear regression model.…”
Section: Personal Resourcesmentioning
confidence: 99%